Laju Biodegradasi Fungisida Oleh Mikroganisme di Dalam Tanah - Alfizar Alfizar (Agricultural Faculty, 2001)
ABSTRACT. In a field garden research soil Faculty of Agriculture, Syiah Kuala University, iprodione biogradation was acceletared following only 2 application of the respective fungicides at the recommended field dosage (750 g rovral/ha). Transformation was detected through 3.5-dichloroanniline production as measured by rapiid colorimettrich method. The degration rates reached a maximum and then stabilized after 5 successive weekly treatments respectively.Key Word :Iprodione; Biodegradation